2017
DOI: 10.2147/cia.s135700
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise on cognitive function in chronic disease patients: a meta-analysis and systematic review of randomized controlled trials

Abstract: BackgroundThe purpose of this study was to conduct a meta-analysis and systematic review to assess the effect of exercise on cognitive function in people with chronic diseases.MethodsPubMed, Web of Science, Embase, the Cochrane Library, CINAHL, PsycINFO, and three Chinese databases were electronically searched for papers that were published until September 2016. This meta-analysis and systematic review included randomized controlled trials that evaluated the effect of exercise on cognitive function compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
36
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 62 publications
(243 reference statements)
3
36
1
1
Order By: Relevance
“…This was probably due to lack of physical activity, which is consistent with previous studies showing that physical activity positively influences cognitive functioning. 28,29) Concomitant use of anxiolytics and hypnotics was significantly associated with less improvement in subjective cognitive symptoms according to the PDQ-K total and attention/concentration scores. Previous studies have found that extensive and prolonged use of benzodiazepines produce cognitive impairment.…”
Section: Discussionmentioning
confidence: 98%
“…This was probably due to lack of physical activity, which is consistent with previous studies showing that physical activity positively influences cognitive functioning. 28,29) Concomitant use of anxiolytics and hypnotics was significantly associated with less improvement in subjective cognitive symptoms according to the PDQ-K total and attention/concentration scores. Previous studies have found that extensive and prolonged use of benzodiazepines produce cognitive impairment.…”
Section: Discussionmentioning
confidence: 98%
“…This was probably due to lack of physical activity, which is consistent with previous studies showing that physical activity positively influences cognitive functioning. 28 , 29) …”
Section: Discussionmentioning
confidence: 99%
“…Importantly, a recent meta-analysis of randomized controlled exercise studies indicates that essentially all forms of exercise improve cognitive function in the elderly ( Cai, Li, Hua, Liu, & Chen, 2017 ), though again, initiation and adherence remain major issues ( Vidoni et al, 2017 ). An alternative strategy, therefore, may be to utilize a passive exercise regimen.…”
Section: Introductionmentioning
confidence: 99%